Effectivity of Virtual Reality to Improve Balance, Motor Function, Activities of Daily Living, and Upper Limb Function in Children with Cerebral Palsy: A Systematic Review and Meta-Analysis - Komariah M; Amirah S; Abdurrahman MF; Handimulya MFS; Platini H; Maulana S; Nugrahani AD; Mulyana AM; Qadous SG; Mediani HS; Mago A (Dove Medical Press, 2024)
Maria Komariah,1,* Shakira Amirah,2,* Muhammad Fahd Abdurrahman,2 Mohammad Farrel Shaquille Handimulya,2 Hesti Platini,3 Sidik Maulana,4 Annisa Dewi Nugrahani,5 Aep Maulid Mulyana,4 Shurouq Ghalib Qadous,6 Henny Suzana Mediani,7 Arpit Mago8 1Department of Fundamental Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia; 2Faculty of Medicine, Universitas Indonesia, Depok, West Java, 16424 Indonesia; 3Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia; 4Master of Nursing Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 5Maternal Fetal Division, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, 40161, Indonesia; 6Department of Nursing and Midwifery, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine; 7Department of Pediatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia; 8Department of Clinical Medicine, Jawaharlal Nehru Medical College, Belagavi, Karnataka, 590010, India*These authors contributed equally to this workCorrespondence: Maria Komariah, Department of Fundamental Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, 45363, Indonesia, Email maria.komariah@unpad.ac.idBackground: Cerebral palsy (CP) is the most common motor disorder in childhood. CP limits movement, which can interfere with children's daily activities. As a technology that provides intensive mass practice to children, virtual reality (VR) can create an interactive and motivating environment. With the intensity set by the therapist and feedback that can be used to produce individualized therapy, VR has great potential to improve CP patients' quality of life, especially in a safe, enjoyable, and playful environment.Purpose: This systematic review and meta-analysis sought to determine the effectiveness of VR for children with CP.Methods: We conducted a comprehensive literature search based on the PRISMA guidelines through PubMed, Scopus, Embase, Wiley, and ProQuest to assess the efficacy of VR in managing children with CP up to 15 September 2022. Risk assessment of bias was performed using Cochrane RoB 2.Results: Nineteen randomized controlled trials with 467 and 427 patients with CP were included in the intervention and control groups in qualitative and quantitative analyses. Participants consisted of cerebral palsy with hemiplegia (n=7), diplegia (n=2), a combination of both (n=4), and undefined (n=13). From all studies conducted, VR showed significant results where VR could improve balance (MD: 2.71[1.95, 3.48]; p < 0.00001), motor function (MD: 3.73 [1.67, 5.79]; p = 0.0004), and activity daily living (MD: 10.05 [2.89, 17.22]. However, VR showed not effective in improving upper limb function.Conclusion: With its advantages and excellent effectiveness, VR may improve functional mobility and the quality of life of children with CP.Keywords: balance, cerebral palsy, children, motor function, virtual reality